Metabolic Reprogramming via Ketogenic Diet: A Novel Approach to Combating Neurological Diseases - Łukasz Mikołaj Karoń; Anna Zygmunt; Karolina Karoń; Wojciech Grabowski; Grzegorz Drapała; Emilia Pedrycz; Daria Pedrycz (Kazimierz Wielki University, 2024)
Epilepsy is a chronic neurological disorder characterized by a persistent tendency for the brain to generate seizures, affecting approximately 0.5-1% of the global population. Despite advances in pharmacological treatments and surgical interventions, around 30% of individuals with epilepsy continue to experience seizures, leading to significant impacts on quality of life. Among these individuals, many suffer from drug-resistant epilepsy (DRE), where seizures persist despite optimal drug therapy or surgical interventions. In recent years, the ketogenic diet (KD)-a high-fat, low-carbohydrate dietary regimen-has emerged as an effective non-pharmacological strategy for managing DRE. The KD works by inducing ketosis, a metabolic state where the body uses fat as the primary energy source instead of carbohydrates, which has been associated with neuroprotective effects and significant seizure reduction. Variants of the KD, such as the Modified Atkins Diet (MAD) and Low Glycemic Index Treatment (LGIT), offer less restrictive alternatives that have shown similar efficacy in reducing seizure frequency. This review explores the cellular and molecular mechanisms of the KD, evaluates its safety and tolerability across different age groups, and assesses its efficacy in treating epilepsy, particularly DRE. The findings underscore the potential of personalized dietary interventions to serve as effective adjunctive therapies in the management of epilepsy, offering new hope for individuals who do not respond to conventional treatments.